Non transfusion dependent thalassemia of pregnancy: a multifaceted approach to maternal and fetal health - Shah, Aashka; Raithatha, Nitin; Goenka, Suraj; Padaliya, Akshay; Mistry, Priya; Pandey, Sangita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Non-transfusion dependent thalassemia (NTDT) patients typically remain asymptomatic until certain triggers, such as pregnancy, necessitate transfusions and increase the risk of pregnancy-related complications if not managed appropriately. We present the case of a 38-year-old female with NTDT, splenectomised at age six, who presented at 17 weeks of gestation with weakness and bipedal edema. She was advised to undergo regular blood transfusions and take aspirin, targeting a haemoglobin level of 9 g/dl. The patient was lost to follow-up and she returned later to underwent an emergency caesarean section at 32 weeks due to absent fetal movements and absence of end-diastolic flow. Postpartum, she experienced thromboembolism and was diagnosed with severe osteoporosis, treated with low molecular weight heparin, calcium, and vitamin D supplements. Pregnancy exacerbates anemia and thrombosis risk in thalassemia patients, leading to complications such as intrauterine fetal death, growth retardation, and spontaneous abortions. Aspirin or low molecular weight heparin, along with blood transfusions, are often required to prevent these complications. Iron chelating agents, contraindicated during pregnancy due to teratogenic risks, are typically recommended post-breastfeeding. Thalassemia also impacts other body systems, including cardiovascular, gastrointestinal, and skeletal systems. Therefore, a multidisciplinary approach with a well-planned treatment regimen and comprehensive family planning counselling is essential for NTDT patients.